Primary care referral for knee MRI in the United Kingdom: Association with demography and subsequent surgical intervention. Issue 7 (13th January 2019) - Jayaram, Prem R.; Sun, Julia; Coombes, Emma; Mackay, James; Kasmai, Bahman; McNamara, Iain; Jones, Andrew P.; Denton, Erika R.E.; Toms, Andoni P.
Abstract : Background: Since 2008 primary care physicians (GPs) in our region have been allowed open access to knee MRI scans. There are questions about whether this changes referral practice and if it is an effective use of resources. Purpose: To describe the change in demographics of patients referred for knee MRI following implementation of a new referral pathway. Study Type: Retrospective observational study. Population: All primary care referrals between 2008 and 2015 for knee MRI from a population of 900, 000. Field Strength/Sequence: Not applicable. Assessment: Demographic profile and number of knee MRI referrals and subsequent arthroscopies. Statistical Tests: Comparisons between urban and rural populations used the t ‐test. Test for normality used Shapiro–Wilks. Comparison between abnormal MRI proportions used a chi‐squared test. Results: There were 23, 928 knee MRI referrals (10, 695 from GPs) between 2000 and 2015. MRI knee referrals rose from 210 in 2008 to 2379 in 2015. The average age of the patient decreased from 46.8 (SD = 14.9) in 2008 to 41.3 (SD = 14.7) in 2015. Conversion to arthroscopy declined from 15.4% to 10.2%, but there was no significant change in abnormal scan proportion. Conversion rates showed no significant difference between rural (9.6%) and urban populations (10.5%). Referral rates were significantly higher in low socioeconomic status areas (47.3% vs. 34.6%). The median referral rate per 1000 patients was 13.8 (interquartile range = 8.4). Referral rates varied widely between practices. Data Conclusion: Despite a large rise in knee MRI referrals from primary care, there has been no substantial change in the age profile, suggesting that there has been no increase in inappropriate referral of elderly patients in whom MRI is unlikely to influence management. A modest decrease in the conversion rate to arthroscopy may be reasonably offset against a decrease in secondary care referrals. Socioeconomic status of the target population must be considered when planning primary care knee MRI services. Level of Evidence: 4 Technical Efficacy Stage: 6 J. Magn. Reson. Imaging 2019.